1992
DOI: 10.3928/0147-7447-19920201-06
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Cerclage: A Method of Preventing Femur Fracture in Uncemented Total Hip Arthroplasty

Abstract: The incidence of femur fracture in noncemented hip arthroplasty has been reported to be between 4.1 % and 27.8%. To quantitate the hoop stress generated during insertion of a femoral broach in total hip arthroplasty and determine the effect of cerclage with both braided cable and wire, we harvested 14 pairs of embalmed cadaver femurs. These were reamed and broached to duplicate the surgical technique of inserting a straight non-cemented femoral component. Group one consisted of eight matched cadaver femurs whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Nwankwo et al 21) in their biomechanical study showed that the prophylactic cerclage of the proximal femur increases hoop resistance, decreases strain across bone during femoral broaching of THA, and plays a clinical role to reduce intraoperative fractures. Similarly, Herzwurm et al 22) and Waligora et al 23) in their cadaveric studies found prophylactic wiring increases not only hoop stress resistance to reduce intraoperative fractures during THA but also rotation and energy to failure in well-fixed press-fit femoral implants to minimize the risk of early periprosthetic fracture. Good radiological and functional outcomes in the present study advocate the use of prophylactic cerclage wiring in hips with poor bone stock as a viable option to offer bone-preserving benefits of short stems in young adults.…”
Section: Discussionmentioning
confidence: 89%
“…Nwankwo et al 21) in their biomechanical study showed that the prophylactic cerclage of the proximal femur increases hoop resistance, decreases strain across bone during femoral broaching of THA, and plays a clinical role to reduce intraoperative fractures. Similarly, Herzwurm et al 22) and Waligora et al 23) in their cadaveric studies found prophylactic wiring increases not only hoop stress resistance to reduce intraoperative fractures during THA but also rotation and energy to failure in well-fixed press-fit femoral implants to minimize the risk of early periprosthetic fracture. Good radiological and functional outcomes in the present study advocate the use of prophylactic cerclage wiring in hips with poor bone stock as a viable option to offer bone-preserving benefits of short stems in young adults.…”
Section: Discussionmentioning
confidence: 89%
“…Despite abundant innovations in implant design and surgical technique, iatrogenic periprosthetic fractures remain a key issue during primary THA affecting between 1.5% and 27.8% of cases [ [16] , [17] , [18] , [19] , [20] ]. It must also be acknowledged that, because many surgeons do not bill for repair of an iatrogenic periprosthetic fracture during primary THA, the true incidence may be higher [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…During cementless THA, it is imperative that surgeons obtain initial mechanical stability of the femoral stem to reduce micromotion and increase bony fixation [ 15 , 16 ]. A known complication during femoral preparation is iatrogenic periprosthetic fracture, which is estimated to occur in 1.5%-27.8% of cases and is more common in uncemented THA [ [16] , [17] , [18] , [19] , [20] , [21] ]. Unrecognized iatrogenic fractures can propagate and decrease initial mechanical stability, [ 22 ] leading to early loosening and revision [ 17 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential concern of compromising infection eradication due to metallic hardware to fix the ETO fragment seems to play a negligible role, especially considering that cerclages are exchanged or removed at the time of reimplantation. The placement of a prophylactic cable distal to the ETO has been advocated for in an attempt to decrease the risk of intraoperative fracture during stem insertion [ 47 ]. In the underlying study, no intraoperative diaphyseal fracture was noticed regardless of the use of a prophylactic cable and all three postoperative fractures occurred in the non-ETO group.…”
Section: Discussionmentioning
confidence: 99%